A syndrome including thumb malformations, microcephaly, short stature, and hypogonadism. Issue 10 (October 1997) - Zlotogora, J; Dagan, J; Ganen, A; Abu-Libdeh, M; Ben-Neriah, Z; Cohen, T
Abstract : We report on eight patients from seven different families affected with a syndrome which includes thumb defects, short stature, microcephaly, and mental retardation. Most of the patients had additional malformations, in particular amenorrhoea and azoospermia in the adults. There were no haematological manifestations and the chromosomes were normal without evidence of breakage even after stimulation. In five of the cases the probands' mother received hormonal treatment before or at the beginning of her pregnancy or both. The syndrome may be inherited as an autosomal recessive trait since the patients included both males and females and their parents were related in most cases. In addition, supporting this possibility, they all originated from a small village which may be considered as an isolate. However, in all cases but one, only one person was affected in each family and there was a significant apparent excess of healthy sibs of the probands. These observations may be the result of the variability of the syndrome or a more complex type of inheritance.